Effect of high hydrostatic pressure on aroma components, amino acids, and fatty acids of Hami melon (Cucumis melo L. var. reticulatus naud.) juice - Longying Pei (Food Science & Nutrition, 2020)
Abstract The changes and relationships between the volatile compounds and fatty acids, and between volatile compounds and free amino acids were analyzed after they were handled by 400 and 500 MPa (45°C/10 min) high hydrostatic pressure (HHP). The volatile components of 31, 30, and 32 were detected in the untreated, 400, and 500 MPa samples, respectively. Unlike the ketones and acids, the three contents, including ester (59.59%–71.34%), alcohol (5.95%–7.56%), and aldehyde (0.36%–1.25%), were greatly changed. While HHP treatment exerted a few effects on the contents of 12 kinds of fatty acids. With the increase in pressure, the contents of palmitic acid, linolenic acid, and α‐linolenic acid were remarkably reduced. The correlations between flavor compounds and amino acids, and between flavor compounds and fatty acids were studied by Pearson's correlation analysis and visualized with using the corrplot package in R software. The analysis showed that the amino acids were positively correlated with (E)‐6‐nonenal, (2E,6Z)‐nona‐2,6‐dienal and (Z)‐6‐nonen‐1‐ol, while they were negatively correlated with nonanal, (Z)‐3‐hexen‐1‐ol and ethyl caproate. Besides, the fatty acids were positively correlated with the esters of 2,3‐butanediol diacetate and 2‐methyl propyl acetate, while they were negatively correlated with (E)‐2‐octenal and (Z)‐6‐nonen‐1‐ol.